2021
DOI: 10.1111/add.15724
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of behavioural smoking cessation interventions for people with severe mental ill health—what works?

Abstract: Background and Aims: People with severe mental ill health smoke more and suffer greater smoking-related morbidity and mortality. Little is known about the effectiveness of behavioural interventions for smoking cessation in this group. This review evaluated randomized controlled trial evidence to measure the effectiveness of behavioural smoking cessation interventions (both digital and non-digital) in people with severe mental ill health. Design: Systematic review and random-effects meta-analysis. We searched b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Nonetheless, it was widely noted that service users' may face additional barriers to making full use of smartphone apps, due to the limited availability and costs of data/WiFi and apps themselves. Recent UK data suggests even those people with SMI own phones at high rates, but lower digital literacy amongst some individuals may be an often unrecognized barrier (Spanakis et al, 2021). MHCPs suggested that apps recommended for use in mental healthcare services should be free for service users, and ideally usable 'offline' to some extent (without constant requirement for internet access to engage with app features).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, it was widely noted that service users' may face additional barriers to making full use of smartphone apps, due to the limited availability and costs of data/WiFi and apps themselves. Recent UK data suggests even those people with SMI own phones at high rates, but lower digital literacy amongst some individuals may be an often unrecognized barrier (Spanakis et al, 2021). MHCPs suggested that apps recommended for use in mental healthcare services should be free for service users, and ideally usable 'offline' to some extent (without constant requirement for internet access to engage with app features).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies tested examined the effects of community-based smoking cessation programmes on smokers with severe mental illness, but none specifically for people with BD ( 87 , 88 ). A variety of psychosocial interventions were examined in these studies, including motivational enhancements, smoking cessation education, cognitive behavioral strategies, and contingency management.…”
Section: Treatment Of Comorbid Bipolar Disorder and Tobacco Use Disordermentioning
confidence: 99%
“…A variety of psychosocial interventions were examined in these studies, including motivational enhancements, smoking cessation education, cognitive behavioral strategies, and contingency management. Meta-analysis of these studies showed that individually tailored face-to face interventions are superior to standard care for smoking cessation, but comparing bespoke digital on-line interventions vs. standard digital on-line interventions did not demonstrate any difference in effectiveness ( 88 ).…”
Section: Treatment Of Comorbid Bipolar Disorder and Tobacco Use Disordermentioning
confidence: 99%
“…105 Pharmacological and behavioral interventions, especially if they are combined, for smoking cessation in individuals with mental illness are effective and therefore should be provided to individuals with PAD and mental illness. 106,107 The use of nicotine replacement therapies, including bupropion, nortriptyline, and varenicline, was investigated in a Cochrane systematic review, 108 which showed that these options are effective in smoking cessation in general and that combinations of different medications and with nicotine replacement therapies did not show a superior effect, although the evidence was inconsistent. The risk of adverse effects from smoking cessation treatment did not differ significantly by the type of medication used in individuals with depression, whereas varenicline combined with behavioral health counseling was seen to be more effective in individuals with depression.…”
Section: Mental Health and Smoking Cessationmentioning
confidence: 99%
“…105 Pharmacological and behavioral interventions, especially if they are combined, for smoking cessation in individuals with mental illness are effective and therefore should be provided to individuals with PAD and mental illness. 106,107…”
Section: Mental Health and Pad Treatment Considerationsmentioning
confidence: 99%